Measurement of Water Depth by the Analytical Plotter - Masry, S. E. (The International Hydrographic Review, 2015)
When an object submerged in water is photographed with a camera in the air, the image-forming rays undergo distinct refraction. The use of conventional photogrammetric plotters in measuring from such photographs can be complicated and inaccurate. The mathematical projection principle of the analytical plotter, on the other hand, allows for the effect of refraction to be accurately calculated during the measurements. With the use of such a plotter continuous and accurate measurement and plotting are, therefore, possible. A method for treatment of refraction was developed and tested using the analytical plotter model AP/2C. The technique can be followed in measuring of hydrological models and mapping of shallow water areas where the bottom appears in the photographs.